AB0565 HOSPITALIZATION IN A COHORT OF PATIENTS WITH IDIOPATHIC INFLAMMATORY MYOPATHY: WHAT IS HAPPENING IN ARGENTINA?. (2nd June 2020) - Arizpe, F.; Cosentino, M.; Costi, A. C.; Martire, V.; Testi, A.; García, M.
Abstract : Background: Inflammatory myopathies are rare diseases that affect multiple organs and systems, with poor prognosis and high in-hospital mortality. (1, 2) In Argentina there are few reported data regarding hospitalization and its outcomes in these patients. Objectives: To analyze the characteristics of hospitalizations and the factors associated with poor outcome in adult patients with Idiopathic Inflammatory Myopathy (IIM). Methods: Retrospective, analytical study. We included patients ≥ 18 years with IIM, according to Bohan and Peter and/or ACR / EULAR 2017 criteria, who were admitted in our hospital between 2003 and 2019 at least once. Sociodemographic and clinical data were recorded. We defined "unfavorable outcome" as the presence of one of the following events: death, mechanical respiratory assistance and/or critical care unit requirement. Continuous variables were compared by Student's or Mann Whitney's T test, and categorical variables by Chi 2 test or Fisher's exact test. Binary logistic regression was performed to identify independent factors associated with an unfavorable outcome. Results: 61 hospitalizations of 40 patients with IIM were evaluated; 67.5% of the patients were female (27/40), with a mean age of 52.5 years (SD± 13). The most frequent reason of admission was for diagnosis (44.3%) followed by disease activity (31.1%). In 78.7% of hospitalizations (48/61) the diagnosis was dermatomyositis. The median of hospitalization days was 14 (IQR 8-30). In 21 out of 61 hospitalizations (34.4%), an unfavorable outcome was observed, of which 17 (80.9%) ended in death. Respiratory muscle involvement (p = 0.01), thrombocytopenia (p < 0.001), treatment with intravenous methylprednisolone pulses (p = 0.032), Intravenous Immunoglobulin (p = 0.001), longer hospitalization (p = 0.001) and severe infections (p = 0.001) were associated with adverse outcomes. In the multivariate analysis, serious infections (OR: 21.7; IC95 1.77 - 266; p = 0.016) and the requirement of Intravenous Immunoglobulin (IVIg) (OR: 54.5; IC95 1.4 - 214; p = 0.033) were found to be independently associated with an unfavorable outcome. Conclusion: IIMs are diseases with high morbidity and mortality rate. In this cohort of hospitalized patients, we found a high percentage of unfavorable outcomes. Seriously ill patients received IVIg more frequently, and severe infections were associated with worse prognosis. References: [1]Selva-O'Callaghan, A., Pinal-Fernandez, I., Trallero-Araguás, E., Milisenda, J. C., Grau-Junyent, J. M., & Mammen, A. L. (2018). Classification and management of adult inflammatory myopathies. The Lancet Neurology, 17(9), 816–828. [2]Wu C, Wang Q, He L, Yang E, Zeng X (2018) Hospitalization mortality and associated risk factors in patients with polymyositis and dermatomyositis: A retrospective case-control study. PLoS ONE 13(2): e0192491. Disclosure of Interests: None declared